A study of user perception on facilities provided at UiTM Shah Alam Libraries / Afiqah Ahsan - Ahsan, Afiqah (Faculty of Architecture, Planning and Surveying, 2013)
The facilities management as an industry has emerged as one of the fastest growing over the decade. In FM the current scope is made through in the relationship of the organization through people, place and process. The purpose of this research is to evaluate the user perception and the facilities provided at the UiTM Shah Alam Libraries. The objective of this research are to study the general facilities provided at the library, to evaluate the perception of the users on the facilities provided at the UiTM Shah Alam libraries and to recommend on how to improve the facilities provided at the UiTM Shah Alam libraries. There are chosen the case study for this research which is Tun Abdul Razak Library 1, Tun Abdul Razak Library 2, Tun Abdul Razak Library 3, Tun Abdul Razak Library 4 and Alam Bina Library, FSPU. Lastly, from the result o.f finding, it can produce the result on the perception of the user on the facilities provided at the UiTM Shah Alam Libraries through the distribution of questionnaire the result and finding can be analyzed.